ESTIMASI RISIKO PORTOFOLIO SAHAM PERUSAHAAN PERKEBUNAN DI BURSA EFEK INDONESIA MENGGUNAKAN VALUE AT RISK NON-NORMAL - Aulia Ikhsan; Tatang Sutisna; Siti Widiati (Jurnal Gaussian, 2023)
Stock investment portfolio aims to minimize the investment risk. However, problems of the portfolio formation are determining funds allocation for each stock and measuring its risk. Fund allocation is determined using the Mean-Variance Efficient Portfolio method, while risk measurement is carried out using Value at Risk (VaR). Nevertheless, problem on VaR is determining a fit distribution which would be involved to obtain quantile values at certain probability. This study discusses way of funds allocation determination and VaR value calculation that is aimed to analyze their impact in estimating the VaR value. The study used stock price return rate data of plantation companies listed on Indonesia Stock Exchange such as Astra Agro Lestari Tbk. (AALI), BISI International Tbk. (BISI), and PP London Sumatra Indonesia Tbk. (LSIP). The result showed BISI stock has high volatility so that its funds allocation is relatively smaller. The distribution identified for portfolio return rate is Logistics Distribution with the estimated parameters  0.0001187447 and 0.008810698. Portfolio VaR value at the 95% confidence level is -0.02582382. We conclude the determination of funds allocation does not minimize risk and the calculation of VaR with distributions do not match the data result a relatively higher VaR value.